Alturas de pastos de capim-marandu na interface solo-planta - Azenha, Mariana Vieira [UNESP] (2014)
The objective of this study was to evaluate the effects of management, defined by grazing heights, on litter decomposition, enzyme activities and CO2 from soil and reserves compounds in plants of palisadegrass swards under continuous stocking. The experiment was conducted at the Faculdade de Ciências Agrárias e Veterinárias, UNESP, Jaboticabal, SP. The experimental area consisted of 20 hectares of palisadegrass and divided into 12 paddocks with areas ranging from 0,7 to 1,3 hectares. The treatments included three sward heights (15, 25 and 35 cm) with four replications and grazing method was a continuous variable stocking, during the year 2011. The bag technique was followed to analyze the litter decomposition, and a simple exponential model was used, using PROC NLIN in SAS. The content of organic matter, carbon and carbon/nitrogen ratio decreased over the incubation time and the concentrations of nitrogen, lignin, phosphorus increased. The grazing intensities not influence the litter decomposition. Data on enzymes, CO2 emissions and reserves compounds were analyzed in a completely randomized design with repeated measures using the MIXED procedure of SAS. Grazing intensities did not affect any of the studied enzyme activities (dehydrogenase, protease, cellulase and arylsulfatase). Significant effects (P<0,05) only of the seasons in the activity of these enzymes. The season also significantly influenced (P<0,05) CO2 emissions from the soil, and these higher emissions was in the summer and spring, and lowest in the fall and winter. Total nonstructural carbohydrates shoot were not influenced by any factor studied. In the roots, the lowest values were observed in summer and higher in winter. The total nitrogen and amino acid nitrogen in the shoots were descending the grazing heights, whereas the highest values were found in summer and spring. Compounds reserves in plants are highly affected ...